Improving comprehensive monitoring of cash flows in the treasury through intelligent information fusion systems applications - Shodmonkulova, Shahlo (GREEN ECONOMY AND DEVELOPMENT, 2024)
This paper explores the application of intelligent information fusion systems in improving the comprehensive monitoring of cash flows within treasury operations. As the digitalization of financial management continues, the integration of these advanced systems has become essential for enhancing transparency, efficiency, and control in cash flow management. The study reviews key theoretical frameworks, such as free cash flow theory, and practical applications of AI and machine learning in optimizing financial processes. The paper also highlights the contributions of Uzbek scholars in integrating intelligent systems into public financial management to ensure greater accuracy and accountability in government treasuries. The findings suggest that intelligent information fusion systems can significantly improve real-time monitoring capabilities and streamline cash flow operations in treasury departments.